(untitled) (Prakriti - The International Multidisciplinary Research Journal, 2026)
Women occupy a vital place in the society. They are considered the first architects and future builders of society, being the first teachers of children. From the last decade’s crime statistics, we see sharp number of crimes registered under ‘cruelty’ by husband and his relatives. Now there are many types of crimes against women reported and recorded like rape, cruelty by husband, relatives, family, society, dowry death, sexual harassment, molestation, etc. expanding the new horizon of research. This research attempts to focus on spatio-temporal analysis of crime against women for the period 2019-2020 of Hansi-I and Hnasi-II block with special reference to rape by state level mapping and trend analysis. Remote sensing (Sentinel-2) satellite data with 30 m spatial resolution have been used for preparation of base map and crime location hot spot of the study area. The study is based on secondary data is collected from civil line Police Station, Hansi for the year of 2018 and 2019. GIS is used to view the hotspot of any type of crime activities. It is very efficient software for identifying the crime hotspot in an easy manner. The result indicate that total 58 number of crime were recorded including rape, domestic violence, sexual harassment, dowry and kidnaping found in study area during 2018. It has been observed that rape, domestic violence, sexual harassment, dowry and kidnaping recoded case 9, 19, 14, 13 and 4 respectively. In 2019 it has been found that 19 domestic violence crimes against women recorded in this year. 9 rape crimes, 14 sexual harassment crimes, 13 dowry crimes and 4 kidnaping crime cases recorded against women. There it emerges that the incidence of crime is associated with the socio-economic and demographic profile of the locality. So some remedies should be implemented in our society.